THE TRANSLATION OF FRIGHTENING EXPRESSIONS IN EDGAR ALLAN POE’S SHORT STORIES - Flora Matahari; Priska Meilasari (Universitas Katolik Widya Mandala Surabaya, 2022)
Frightening expressions are the ones causing fear. Fear in any narrative story is very important. Accordingly, this research was aimed at analyzing the type of translation techniques and translation ideology on frightening expressions in Edgar Allan Poe’s short stories. This research applied Molina & Albir’s (2002) theory of translation technique. The theories of translation ideology by Venutti (2000) and Hoed’s (2003) were employed in this research as well. This research was qualitative descriptive. The data collection technique was document analysis. It is conducted by analyzing the frightening expressions in two original short stories entitled The Black Cat and The Fall of The House of Usher and their Indonesian translation entitled Kucing Hitam and Misteri Rumah Keluarga Usher. The result was that there were fourteen out of twenty-four types of translation techniques. This included Discursive Creation, Established Equivalence, Deletion, Generalization, Modulation, Addition, Explicitation, Paraphrase, Particularization, Adaptation, Concision, Description, Transposition, and Compensation. The dominant type of translation technique is Establish Equivalence. The most dominant translation techniques in The Black Cat were established equivalence while the most dominant techniques in The Fall of the House of Usher were discursive creation. Both the translations of frightening expressions in The Black Cat and The Fall of the House of Usher grasped domestication ideology.